2019
DOI: 10.1002/jbmr.3881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Duration Spaceflight on Vertebral Strength and Risk of Spine Fracture

Abstract: Although the negative impact of long-duration spaceflight on spine BMD has been reported, its impact on vertebral strength and risk of vertebral fracture remains unknown. This study examined 17 crewmembers with long-duration service on the International Space Station in whom computed tomography (CT) scans of the lumbar spine (L 1 and L 2 ) were collected preflight, immediately postflight and 1 to 4 years after return to Earth. We assessed vertebral strength via CT-based finite element analysis (CT-FEA) and spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
1
5
0
2
Order By: Relevance
“…Earlier studies demonstrated a reduction in BMD of 0.5–1.5% per month in space [ 6 , 7 ]. This finding was supported by Burkhart et al, who reported a monthly reduction of 0.5–1% in BMD on the ISS in humans [ 43 ]. However, Bilancio et al reported only a 0.9–1.4% decrease in total BMD after 6 months on the ISS in humans [ 42 ].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Earlier studies demonstrated a reduction in BMD of 0.5–1.5% per month in space [ 6 , 7 ]. This finding was supported by Burkhart et al, who reported a monthly reduction of 0.5–1% in BMD on the ISS in humans [ 43 ]. However, Bilancio et al reported only a 0.9–1.4% decrease in total BMD after 6 months on the ISS in humans [ 42 ].…”
Section: Discussionsupporting
confidence: 67%
“…BMD was decreased in humans by 0.9% after 6 months [ 42 ] and 1% per month in space [ 43 ]. The decrease in BMD in animals was 18–35.7% after 1 month [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The longer exploration space missions will bring new challenges to musculoskeletal health. One of the first steps to be taken in the coming years is to understand whether the musculoskeletal adaptations observed on missions of several months 3 , 19 – 22 can be extrapolated to space missions of more than twelve months. Recent studies that examined bone health during the recovery phase suggest that bone atrophy and functional decline persist well beyond return from space 20 , 22 .…”
Section: Targeted Periods Of Observationmentioning
confidence: 99%
“…In einer kürzlich durchgeführten Studie wurde eine 11-prozentige Verringerung der Lendenlordose unmittelbar nach der Rückkehr von einer langen ISS-Mission festgestellt 38 . Nachuntersuchungen, durchgeführt nach einem und 2 Jahren, zeigten eine Normalisierung der Wirbelsäulenverkrümmung zu ihrem Zustand vor der Mission 38 . Ebenso wurde eine abgeflachte Lordose nach einer Bettruhestudie festgestellt, die zudem zeigte, dass die obere Lendenwirbelsäule lordotischer wurde 39 .…”
Section: Rückengesundheit Im Allunclassified
“…Eine Erklärung dafür könnte die Abflachung der Wirbelsäule sein. In einer kürzlich durchgeführten Studie wurde eine 11-prozentige Verringerung der Lendenlordose unmittelbar nach der Rückkehr von einer langen ISS-Mission festgestellt [38]. Nachuntersuchungen, durchgeführt nach einem und 2 Jahren, zeigten eine Normalisierung der Wirbelsäulenverkrümmung zu ihrem Zustand vor der Mission [38].…”
Section: Brustwirbelsäuleunclassified